2018
DOI: 10.21037/jtd.2018.09.74
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic dysfunction in patients with obesity hypoventilation syndrome

Abstract: Background: Obesity hypoventilation syndrome (OHS) can be complicated by several cardiovascular conditions. We assessed the prevalence and factors associated with left ventricular diastolic dysfunction (LVDD) in patients with OHS. Methods: In this prospective observational study, all consecutive OHS patients referred to the sleep disorders clinic between January 2002 to December 2016 were included (n=113). Demographic data, echocardiography, sleep parameters, arterial blood gases (ABGs), and lung functions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…OHS patients are at an increased risk of developing heart failure, ventricular dysfunction, cor pulmonale, pulmonary hypertension, and angina pectoris than obese eucapnic individuals [ 18 ]. A study found that the prevalence of left ventricular dysfunction was high in OHS patients even with mild to moderate OSA [ 19 ]. Prior studies reveal that OHS patients have a high prevalence of right ventricular dysfunction, left ventricular hypertrophy, arrhythmias, and pulmonary hypertension due to a reflex elevation of arterial blood pressure and increased heart workload following chronic hypoxia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…OHS patients are at an increased risk of developing heart failure, ventricular dysfunction, cor pulmonale, pulmonary hypertension, and angina pectoris than obese eucapnic individuals [ 18 ]. A study found that the prevalence of left ventricular dysfunction was high in OHS patients even with mild to moderate OSA [ 19 ]. Prior studies reveal that OHS patients have a high prevalence of right ventricular dysfunction, left ventricular hypertrophy, arrhythmias, and pulmonary hypertension due to a reflex elevation of arterial blood pressure and increased heart workload following chronic hypoxia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al Otair and his colleagues found positive correlation between PaCO2 and LVDD and negative correlation between PaO2 and LVDD in OSA patients but without significant difference (Al Otair et al, 2018). These data may partly depend on the patient selection and use of only conventional Doppler, which is not accurate for detecting early diastolic dysfunction in patients with a normal ejection fraction (EF) (Ommen et al, 2000).…”
Section: Datamentioning
confidence: 99%